SCREENING AND CHARACTERIZATION OF L-GLUTAMINASE PRODUCED BY BACTERIA ISOLATED FROM SANGIHE TALAUD SEA - Ekowati Chasanah; Usman Sumo Friend Tambunan; Tanti Yulianti (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2012)
L-glutaminase (L-glutamine amidohydrolase, EC 3.5.1.2) is a very important enzyme due to its role as flavor enhancer and antileukemic agent. Salt-tolerant L-glutaminase produced bymarine bacteria is favorable in food industries. This study describes the screening of L- glutaminase producing marine bacteria from Sangihe-Talaud Sea, North Sulawesi, Indonesia.Screening of L-glutaminase was performed using a liquid medium and identification of selected isolate was  performed using molecular-based 16S rDNA. Results showed that there were 7 isolates produced positive results of L-glutaminase, and one of them (II.1 isolate) produced the highest activity, i.e 147.99 U/L, equivalent to the specific activity of 62.32 U/mg. The isolate then selected for further study. Bacterial identification based on 16S rRNA sequencing has revealed that the isolate was 96% similar to Pseudomonas aeruginosa strain CG-T8. Characterization of extracellular L-glutaminase from the II.1 isolate showed that the enzyme worked optimally at temperature  of 37-45 °C and pH 7. The enzyme was stable when NaCl solution was added up to 8% and  began to decrease on addition of NaCl solution of 16% and 20% with relative activity of 79% and 74%, respectively. The effect of metal ions, e.g Mn2+, Mg2+, and Co2+ in the form of chloride salt, were able to increase enzyme activity, whereas the addition of other metal ions (Zn2+, Fe3+, and Ca2+) decreased the activity. The molecular weights of L-glutaminase was estimated around42 kDa and 145 kDa.